Strategi Komunikasi Pemasaran PDAM Tirta Binangun dalam Memasarkan Produk AMDK AirKU - Muhammad Rahman Aziz; Iva Vikrani Deslia (CV. ITTC INDONESIA, 2025)
PDAM Tirta Binangun Kulon Progo is experiencing problems in marketing their product, namely bottled drinking water with the AirKU brand, in an increasingly modern era and competition with many giant bottled drinking water companies circulating in the market. This study aims to describe and analyze the effectiveness of the implementation of marketing communication strategies used by PDAM Tirta Binangun Kulon Progo in increasing sales of AirKU bottled drinking water products. This study employed a qualitative descriptive method using the 7P marketing mix, which includes product, price, promotion, place, people, process, and physical evidence. Data collection techniques included in-depth interviews with two informants selected using purposive sampling. The research results show that the strategies used can strengthen local brand identity, reach more customers through structured promotion and distribution methods, and build consumer trust through product quality and certification. The results of this study are expected to provide significant contributions both academically and practically. Academically, this study enriches the literature on the marketing communication mix (marketing mix 7P). Practically, this study is expected to be the basis for the development of PDAM Tirta Binangun to support marketing communications as a reference for marketing and increasing sales of AirKU bottled drinking water products, as well as other companies that want to increase their product sales. This study recommends the development of sustainable strategies to maintain AirKU's competitiveness in the increasingly competitive bottled drinking water market.